SURG-04. SURVIVAL BENEFIT ASSOCIATED WITH GROSS TOTAL RESECTION IN GRADE II ASTROCYTOMAS: AN INTEGRATED ANALYSIS OF THE SEER AND TCGA DATABASE. (5th November 2018) - Alattar, Ali; Carroll, Kate; Bryant, Alex; Hirshman, Brian; Joshi, Rushikesh; Carter, Bob; Harismendy, Olivier; Chen, Clark
Abstract: We used the Surveillance, Epidemiology, and End Results (SEER) to determine the survival benefit associated with gross-total resection (GTR) of grade II diffuse astrocytoma (DA) stratified by age and tumor location. We further correlated these findings to the prevalence of isocitrate dehydrogenase mutations (mIDH) in similarly age- and location-stratified DA patients from The Cancer Genome Atlas (TCGA). The SEER database was used to assess GTR associated survival benefits relative to subtotal resection (STR), and TCGA database was used to determine the prevalence of IDH mutation. Survival analysis was accomplished using Kaplan-Meier curves, log-rank tests, and multivariable Cox proportional hazards models. GTR was associated with significant survival benefit for all DA patients with frontal tumors irrespective of age (age < 50, HR 0.56, p=0.002; age > 50, HR 0.41, p< 0.001). However, in patients with non-frontal tumors, only those < 50 derived a survival benefit from GTR (< 50 HR 0.55, 95%, p=0.002; > 50 HR 0.78, 95% p=0.114). This pattern of GTR-associated survival in DA patients differed significantly from our previous finding in AA patients, where significant survival benefit was only observed in patients < 50 with frontal tumors who underwent GTR. While the prevalence of mIDH status in the TCGA DA and AA's generally tracked with the above described survival patterns, notable exceptions were observed. For instance, while the prevalence of mIDH in patients age > 50 with non-frontal tumor were comparable for DA and AAs (82% versus 75%), the GTR associated survival benefit in these patients differed significantly. Our results suggest that the survival benefit of GTR, prevalence of mIDH, and relationship of these variables to patient age and tumor location differs between DA and AA. While mIDH status generally correlated with survival patterns, instances where these patterns differed suggests complex interactions between age, location, mIDH status and tumor grade as prognostic factors.